Analysis of Delaminated Composite Plates Using 3D Degenerated Plate Element Considering Geometric Non-Linearity - Pratik Tiwari; Swarup K. Barman; Changduk Kong; Sungjin Ahn; Hyunbum Park (Applied Sciences)
This paper presents a numerical investigation of delaminated composite plates using a 3D degenerated plate element, with a focus on geometric nonlinearity. An 8-noded degenerated element is used to model the composite plate, ensuring higher accuracy and computational efficiency. Delamination is modeled using Heaviside step functions, providing a clear representation of discontinuities. The Green–Lagrangian formulation is employed to incorporate geometric nonlinearity and to evaluate its effects on the deflection behavior of delaminated plates under load. The developed model is validated against existing literature, demonstrating its reliability. Subsequently, a comprehensive parametric study is conducted to evaluate the influence of various factors including lamina sequences, boundary conditions, load intensities, and the size and location of the delamination (considered at the center of the laminate). A uniformly distributed pressure load is applied across the entire plate to simulate realistic loading conditions. Additionally, the effects of multiple delaminations through the thickness of the laminate are explored, with key observations on their impact reported. The findings provide valuable insights into the structural performance of delaminated composite plates under nonlinear conditions.